2011
DOI: 10.1111/j.1365-2850.2011.01784.x
|View full text |Cite
|
Sign up to set email alerts
|

Models of care delivery in mental health nursing practice: a mixed method study

Abstract: The aim of this study was to identify the conceptual models that underpin mental health nursing care in clinical settings. This study is a modification of a previous study which evaluated the influence of implicit models of mental disorder on processes of decision making within community-based teams. Participants completed questionnaires in response to a scenario. A range of explanatory conceptual models were identified in respect to aetiology, treatment and recovery. In a forced choice the participants ranked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 36 publications
1
27
0
5
Order By: Relevance
“…However, participants in the current study embraced a medical approach to mental health nursing. It has been noted that mental health nurses, despite acknowledging that mental distress is influenced by social/psychodynamic factors, are often constrained by the dominance of the medical model (Carlyle et al ). Hornik‐Lurie et al () reported that mental health nurses only interact with clients for brief periods, often occurs during medication rounds, while other care professionals – such as social workers – spend more time with service users.…”
Section: Discussionmentioning
confidence: 99%
“…However, participants in the current study embraced a medical approach to mental health nursing. It has been noted that mental health nurses, despite acknowledging that mental distress is influenced by social/psychodynamic factors, are often constrained by the dominance of the medical model (Carlyle et al ). Hornik‐Lurie et al () reported that mental health nurses only interact with clients for brief periods, often occurs during medication rounds, while other care professionals – such as social workers – spend more time with service users.…”
Section: Discussionmentioning
confidence: 99%
“…While MHN have shown adaptability to the many systemic changes over the past 20 years, their roles are being increasingly narrowed towards safe containment of consumers, rather than offering therapy‐based interventions within inpatient settings dominated by medicine‐based psychiatry (Carlyle et al . ; Cleary et al . ; Browne et al .…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been noted that some mental health nurses can be placed in conflicting situations in that they regard mental distress as stemming from psychodynamic or interpersonal issues but are constrained to biomedical roles (Carlyle et al . ). For Barker (), personal process mental health nursing would involve an unconscious perception of patients' problems.…”
Section: The Abject and Mental Health Nursing Knowledge And Practicementioning
confidence: 97%
“…, Merritt & Proctor ) Integrated models and theories; the therapeutic relationship and intersubjectivity (Armstrong & Kelly , Walker , Wilshaw , Pierson , O'Brien , Dziopa & Ahern , Carlyle et al . , McCrae , Browne et al . )…”
Section: The Abject and Mental Health Nursing Knowledge And Practicementioning
confidence: 99%